Pathogenic mechanisms of autoantibodies - Kallenberg, Cees (Henry Stewart Talks, 2007)
Loss of tolerance for "self", Immune response to "self", Self destruction, Etiology of autoimmune diseases: endogenous and exogenous factors, Mechanisms of autoimmunity, The spectrum of autoimmune diseases, Organ-specific and non-organ-specific disorders, Overlap of autoantibodies, Anti-thyroid antibodies, Pathogenic immune responses, Systemic autoimmune diseases, Anti-GMB and Goodpasture's syndrome, Anti-C1q, ANCA-associated vasculitis
Archived at 2020/06/30